Pendampingan Pembuatan Sistem Informasi Pengaduan Masyarakat Berbasis Website Desa Karang Baru Timur - Jumawal; Muhammad Royyan; Muh. Miftahussyurur mz; Isupianto; Zaky (Universitas Hamzanwadi, 2025)
This community service activity aimed to assist Karang Baru Timur Village in developing a website-based Community Complaint Information System as a solution to improve the quality of public services and enhance transparency in village governance. The main problem faced by the village was that the complaint submission process was previously conducted manually, unstructured, and difficult to track. The proposed solution involved designing and implementing a website-based complaint information system that enables centralized, validated, and traceable documentation of community reports. Through the stages of needs observation, system design, implementation, and training, a website was developed to facilitate community complaint submission and provide report management features for village administrators. The system is also equipped with a National Identification Number (NIK) management feature to ensure the validity of complainant data. The testing results showed that all main system functions operated properly according to the defined scenarios, including complaint submission, data validation, report processing, and status tracking. The impact of this activity is reflected in increased efficiency of village administrative services, improved organization of complaint documentation, and greater ease and participation of the community in submitting complaints in a transparent and structured manner. Therefore, this system has the potential to serve as a long-term solution for promoting modern, responsive, and transparent public services at the village level.